A management perspective on energy efficient renovations in Swedish multi-family buildings. (October 2017) - Nair, Gireesh; Azizi, Shoaib; Olofsson, Thomas
Abstract: Sweden has around 2.5 million dwellings in multi-family buildings, which constitute about 55% of the total dwelling units. The multi-family building ownership in Sweden can be categorized into municipal, private and co-operative ownership. Approximately 40% of apartments in multi-family buildings belong to municipal housing companies, while the rest is equally shared by private companies and co-operative housing associations. These organizations have different priorities, limitations and concerns related to energy renovations. Accordingly, in this sector the decisions to invest in energy efficiency improvement depends to a large extent on the type of ownership. In this study we analyzed the perspectives of different types of building ownership on energy efficient renovation. The analysis is based on detailed interviews of 4 senior managers representing the multi-family buildings under different ownership categories. Along with this we also interviewed a municipality energy adviser. All the interviewees are based in in North Sweden. The drivers to facilitate the rate of adoption of energy renovation in such buildings are discussed.